2007
DOI: 10.1084/jem.20061968
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lymphotoxin-αβ on antigen-specific T cells is required for DC function

Abstract: During an immune response, activated antigen (Ag)-specific T cells condition dendritic cells (DCs) to enhance DC function and survival within the inflamed draining lymph node (LN). It has been difficult to ascertain the role of the tumor necrosis factor (TNF) superfamily member lymphotoxin-αβ (LTαβ) in this process because signaling through the LTβ-receptor (LTβR) controls multiple aspects of lymphoid tissue organization. To resolve this, we have used an in vivo system where the expression of TNF family ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 37 publications
2
70
0
Order By: Relevance
“…Thus, thymic migration and localization of DCs may not rely on the CCR7-CCR7L chemotaxis and is unlikely to be a major contributor to impaired thymic negative selection in our Ltbr Ϫ/Ϫ mice. Whether our Ltbr Ϫ/Ϫ DCs have an intrinsic functional defect that contributes to the Ltbr Ϫ/Ϫ phenotype, as was suggested recently (38), remains an interesting question for future study.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, thymic migration and localization of DCs may not rely on the CCR7-CCR7L chemotaxis and is unlikely to be a major contributor to impaired thymic negative selection in our Ltbr Ϫ/Ϫ mice. Whether our Ltbr Ϫ/Ϫ DCs have an intrinsic functional defect that contributes to the Ltbr Ϫ/Ϫ phenotype, as was suggested recently (38), remains an interesting question for future study.…”
Section: Discussionmentioning
confidence: 73%
“…Their result also indicated that DC are dysfunctional without LTα 1 β 2 or CD40 ligand expression on antigen-activated T cells. However, signaling through either CD40 or LTβR restored DC function, suggesting that both pathways cooperates to optimize DC "conditioning" [52] . CD40 and LTβR are quite similar in their mechanisms of signaling, utilizing TRAF adaptors and competent in noncanonical NFκB signaling, although unlike LTβR, CD40 activates TRAF6 pathways.…”
Section: Functions In Host Defense Regulated By Tnfr Superfamilymentioning
confidence: 99%
“…Bone marrow-derived mast cells express LTβR and triggering of LTβR signaling using physiological or pharmacological approaches induced the production of cytokines and pro-inflammatory chemokines [51]. The group of J. Gommerman demonstrated that LTα 1 β 2 expression in antigen-specific T cells was required for optimal DC function [52]. Their result also indicated that DC are dysfunctional without LTα 1 β 2 or CD40 ligand expression on antigen-activated T cells.…”
Section: Functions In Host Defense Regulated By Tnfr Superfamilymentioning
confidence: 99%
“…Thus, tumor antigens that are cross-presented by mature DCs are more likely to induce tumor immunity. A recent study has shown that global LTβR signaling is required for maximal expression of CD86 on Ag-bearing DC and for efficient priming of T cells, and that the LTβR signaling on the DCs is essential to condition them for T cell priming [63]. Moreover, the DCs that become non-functional in the absence of CD40L, an important signal for DC maturation, on Ag-specific T cells can be overcome by stimulating LTβR [63].…”
Section: Light Regulates Dcs At the Tumor Site To Promote Primingmentioning
confidence: 99%
“…A recent study has shown that global LTβR signaling is required for maximal expression of CD86 on Ag-bearing DC and for efficient priming of T cells, and that the LTβR signaling on the DCs is essential to condition them for T cell priming [63]. Moreover, the DCs that become non-functional in the absence of CD40L, an important signal for DC maturation, on Ag-specific T cells can be overcome by stimulating LTβR [63]. This observation is consistent with previous findings that LIGHT can cooperate with CD40L to induce the maturation of monocyte-derived DCs [64].…”
Section: Light Regulates Dcs At the Tumor Site To Promote Primingmentioning
confidence: 99%